Power Flow Maximization in Permanent-Magnet Generators - Catuogno, Guillermo Ricardo (2014)
The main hypothesis proposed in this paper is that by controlling the harmonic and zero-sequence components of the current in nonsinusoidal permanent-magnet synchronous generators (PMGs), additional energy can be obtained, thereby increasing the machine power density without increasing the Joule effect losses. Two different strategies are proposed for three- and four-wire topologies; therefore, four different cases are analyzed. The strategies consist in controlling the PMG stator currents, following a function that depends on the waveform of the back electromotive force (EMF). The current function is obtained from the instantaneous reactive power theory. An experimental system was built to validate the proposal. Experimental results prove that it is possible to increase power in a tested PMG by 7% using the four-wire topology in comparison with the conventional block commutation and same losses. Higher power gain can be obtained for machines with almost rectangular-shaped EMF waveforms.